LC-MS Based Metabolite Profiling of Ethanolic Extracts from Curcuma domestica Val. varieties Turina-1 - Mulyani Sri; Harsojuwono Ahmadi Bambang; Antara Semadi I Nyoman; Putra Kencana I Nengah (Agroindustrial Journal, 2020)
It is important to know the metabolite compounds profile of Curcuma domestica Val. varieties Turina-1, as one of the superior varieties of turmeric, so that it can be utilized better. Therefore, the purpose of this research is to study the metabolite profile of ethanol extract of Curcuma domestica Val. Varieties Turina-1. The samples for this research were obtained from BPPT Bogor-Indonesia. These samples were extracted using ethanol (96 %) and then analyzed using UPLC-QToF-MS / MS System (Waters), mass spectrometry: XEVO-G2QTOF (Waters), in ESI positive resolution mode, using gradient method with mobile phase: water, formic acid and acetonitrile. The study found 13 metabolite compounds: Demethoxycurcumin-2 (48.23%), α- Turmerone (19.623%), Curcumin (18.550%), Bisdemethoxycurcumin-3 (9.064%), Curcumin-1, (1.706%), and compounds others with less than 1% (Kaempferol 3-O-glucosyl-rhamnosylgalactoside, Demethoxycurcumin, ar-Turmerone Bisdemethoxycurcumin, a-Terpinolene, LTyrosine and L-Alanine, L-serine). Based on this research, the main metabolite compound contained in the ethanol extract of Curcuma domestica Val. varieties Turina-1 that has the potential as antioxidants is the curcuminoids.